The application of intraoral radiography to assess the success of prosthodontic treatment: Pengaplikasian radiografi intraoral dalam menilai keberhasilan perawatan prostodontik - Barunawaty Yunus; Muthia Mutmainnah Bachtiar; Astri Al-hutami Aziz; Muhammad Iswanto Sabirin (Makassar Dental Journal PDGI Makassar, 2021)
Background: Intraoral radiography is a radiographic technique that is often used in dentistry. Almost all dental and oral care re-quires radiographic examination data to support optimal results. Intraoral periapical radiographs can be helpful and very import-ant in estimating the mesiodistal dimensions of the potential area for implant placement and for obtaining an initial estimate of the vertical dimension. Objective: to understand the use of intraoral radiography in prosthodontics. Conclusion: the use of in-traoral radiography has enormous benefits for rehabilitation treatment, especially in prosthodontics, be it the use of periapical, bitewing and occlusal techniques.